Transforming Karachi into a Livable and Competitive Megacity : A City Diagnostic and Transformation Strategy - World Bank (Washington, DC: World Bank, 2018)
With a population of 16 million, Karachi is the largest megacity in Pakistan. Despite being a large city that is home to many, it has seen a substantial decline in quality of life and economic competitiveness in recent decades. Basic service delivery is very poor, with very low indicators for water supply, sanitation, public transport and public spaces. Pollution levels are high, and the city is vulnerable to disasters and climate change. A highly complex political economy, institutional fragmentation, land contestation, crime and security issues and social exclusion exacerbate these issues and make city management challenging.